Theoretical Bending Collapse of Hat-Section Tubes - Hashim, Hafizan; Hashim, Hanita; Affendi Jamal, Arif; A.M. Jusoh, M. (International Journal of Engineering and Technology, 2018)
This paper presents an attempt to modify an existing theoretical model to predict the bending collapse response of hat-section tubular structures. The analytical collapse model was based on Kim and Reid. Additional hinge lines created during deformation of the tube were examined and integrated with existing model to forming a modified analytical solution. Variation of the hinge moments were solved using limit analysis technique. Procedure for developing the finite element (FE) models of tube specimens was also presented. Moment-rotation characteristics from pure bending simulation were compared with analytical model and good agreement was achieved. The average of differences between simulation and calculation were found to be <5% within plastic region. In conclusion, the modified analytical solution has adequate capability to predict the moment-rotation relationship of hat-section tubes subject to pure bending..Â